CAY10683 and imatinib have synergistic effects in overcoming imatinib resistance via HDAC2 inhibition in chronic myeloid leukemia. Issue 2 (3rd January 2020) - Zhang, Tianzhuo; Wei, Danna; Lu, Tingting; Ma, Dan; Yu, Kunlin; Fang, Qin; Zhang, Zhaoyuan; Wang, Weili; Wang, Jishi
Abstract : Imatinib (IM) is utilized for targeting the BCR–ABL fusion protein and as such, chronic myeloid leukemia (CML) is considered to be a curable disorder for which patients can achieve a long survival. Abstract : Imatinib (IM) is utilized for targeting the BCR–ABL fusion protein and as such, chronic myeloid leukemia (CML) is considered to be a curable disorder for which patients can achieve a long survival. However, 15–20% CML cases end up with IM resistance that will develop into the accelerated stage and eventually the blast crisis, thereby restricting the treatment choices and giving rise to a dismal survival rate. Histone deacetylases (HDACs) have been identified to modulate the oncogene as well as tumor suppressor gene activities, and they play crucial parts in tumorigenesis. It is found recently that IM combined with HDAC inhibitors (HDACi) can serve as a promising means of overcoming IM resistance in CML cases. Santacruzamate A (CAY10683) has been developed as one of the selective and powerful HDACi to resist HDAC2. Therefore, in this study, we aimed to examine whether CAY10683 combined with IM could serve as the candidate antitumor treatment for CML cases with IM resistance. The influences of CAY10683 combined with IM on the cell cycle arrest, apoptosis, and viability of CML cells with IM resistance were investigated, and it was discovered that the combined treatment exerted synergistic effects on managing the IM resistance. Moreover, further studies indicated that CAY10683 combined with IM mainly exerted synergistic effects through inhibiting HDAC2 in K562-R and LAMA84-R cells with IM resistance. Besides, the PI3K/Akt signal transduction pathway was found to mediate the HDAC2 regulation of CML cells with IM resistance. Eventually, it was also discovered, based on the xenograft mouse model, that the combined treatment dramatically suppressed CML proliferation in vivo . To sum up, findings in the current study indicate that CAY10683 combined with IM can be potentially used as the candidate treatment for CML with IM resistance.